The Challenges of Telemedicine in Rheumatology - Song, Yujie; Bernard, Laurène; Jorgensen, Christian; Dusfour, Gilles; Pers, Yves-Marie (Frontiers in Medicine, 2021)
During the past 20 years, the development of telemedicine has accelerated due to the rapid advancement and implementation of more sophisticated connected technologies. In rheumatology, e-health interventions in the diagnosis, monitoring and mentoring of rheumatic diseases are applied in different forms: teleconsultation and telecommunications, mobile applications, mobile devices, digital therapy, and artificial intelligence or machine learning. Telemedicine offers several advantages, in particular by facilitating access to healthcare and providing personalized and continuous patient monitoring. However, some limitations remain to be solved, such as data security, legal problems, reimbursement method, accessibility as well as the application of recommendations in the development of the tools.